2017
DOI: 10.1016/j.pdpdt.2016.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Visible light enhances the antimicrobial effect of some essential oils

Abstract: The photodisinfection is a topical, broad spectrum antimicrobial technology, targeting bacteria, virus, fungi, and protozoa effective for single cells as for biofilms. Natural molecules have been studied less than synthetic agents in the process but they are currently receiving great interest. Therefore, the aim of this study is to evaluate for the first time if non-coherent blue and red light enhances the antimicrobial activity of some essential oils when standard strains for antibiotic or fungicide tests are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 30 publications
(31 reference statements)
0
10
0
2
Order By: Relevance
“…These extracts are currently used to inactivate the bacteria causing foodborne disease (Diao et al, 2013). In a study exploring the combination therapy of aBL with some essential oils, Marques-Calvo et al reported that aBL at 460–470 nm enhanced the antimicrobial activities of the clove and thyme oils against S. epidermidis , P. aeruginosa , and C. albicans (Marques-Calvo et al, 2016). In the study, essential oils were at 0.5% or 5% concentration.…”
Section: Synergism Of Antimicrobial Blue Light With Other Agentsmentioning
confidence: 99%
“…These extracts are currently used to inactivate the bacteria causing foodborne disease (Diao et al, 2013). In a study exploring the combination therapy of aBL with some essential oils, Marques-Calvo et al reported that aBL at 460–470 nm enhanced the antimicrobial activities of the clove and thyme oils against S. epidermidis , P. aeruginosa , and C. albicans (Marques-Calvo et al, 2016). In the study, essential oils were at 0.5% or 5% concentration.…”
Section: Synergism Of Antimicrobial Blue Light With Other Agentsmentioning
confidence: 99%
“…One study found that essential oils derived from eucalyptus (5%), clove (0.5%) and thyme (0.5%) improved the blue light (469–470 nm) inactivation of S. epidermidis and P. aeruginosa by 2–7 and 3–8 log CFU/mL, respectively, as compared with inactivation achieved by light alone. Relative to treatments with essential oils alone, samples treated with the combination of essential oils and blue light had 3–6 and 3–5 log CFU/mL lower counts of S. epidermidis and P. aeruginosa , respectively [ 238 ].…”
Section: Hurdle Technologymentioning
confidence: 99%
“…Several studies have shown that oral bacteria are sensitive to PDT in planktonic cultures. Recent studies have reported that PDT induced bacterial cell destruction and reduced bacterial counts by more than 10-fold in biofilms of Streptococcus mutants [ 22 , 23 , 24 , 25 , 26 ], Streptococcus sobrinus and Streptococcus sanguinis , using toluidine blue or erythrosine as a photosensitizer [ 2 , 27 , 28 ], silver nanoclusters/rose Bengal nanocomposite [ 22 ], curcumin and methylene blue [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was also desired to test the efficiency of photodynamic antimicrobial therapy on extracted teeth by scanning electron microscopy. As far as we know there is only one study that demonstrates the efficiency of photodynamic therapy using essential oils of eucalyptus ( Eucalyptus radiata ), clove ( Eugenia caryophyllata ) and thyme ( Thymus vulgaris ) on Staphylococcus epidermidis (CECT 231), Pseudomonas aeruginosa (CECT 110), and Candida albicans (1392) [ 25 ]. Marqués-Calvo et al [ 25 ] concluded that the photodynamic activity depends on the oil concentration and light source (red or blue light) and that phenols (eugenol and thymol) were the most potent antimicrobial agents, underlining that light exposure improved antimicrobial activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation